2018
DOI: 10.1111/1475-6773.12823
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 340B Drug Pricing Program on Cancer Care Site and Spending in Medicare

Abstract: Objective To examine the impact of the 340B drug discount program on the site of cancer drug administration and cancer care spending in Medicare. Data Sources/Study Setting 2010–2013 Medicare claims data for a random sample of Medicare Fee‐for‐Service beneficiaries with cancer. Study Design We identified the 340B effect using variation in the availability of 340B hospitals across markets. We considered beneficiaries from markets that newly gained a 340B hospital during the study period (new 340B markets) as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…In other work, authors found the probability of cancer drug administration occurring in hospital outpatient departments (HOPDs) versus physician offices increased 7.8 percentage points more in new 340B markets. That same study found no increase in drug spending for Medicare patients receiving care at a 340B facility, but an increase in Medicare payments for other cancer care of $1162 in markets newly gaining a 340B hospital compared with markets with no 340B hospital (an 8.4 percent increase) …”
Section: Impact Of 340b On Care Patternsmentioning
confidence: 92%
See 1 more Smart Citation
“…In other work, authors found the probability of cancer drug administration occurring in hospital outpatient departments (HOPDs) versus physician offices increased 7.8 percentage points more in new 340B markets. That same study found no increase in drug spending for Medicare patients receiving care at a 340B facility, but an increase in Medicare payments for other cancer care of $1162 in markets newly gaining a 340B hospital compared with markets with no 340B hospital (an 8.4 percent increase) …”
Section: Impact Of 340b On Care Patternsmentioning
confidence: 92%
“…That same study found no increase in drug spending for Medicare patients receiving care at a 340B facility, but an increase in Medicare payments for other cancer care of $1162 in markets newly gaining a 340B hospital compared with markets with no 340B hospital (an 8.4 percent increase). 22 Overall, MedPAC reported that in the period 2012 to 2017, the volume of outpatient prospective payment system (OPPS) clinic vis- 24 In this case, the hepatitis C treatment was a supply of oral medications dispensed by 340B providers which could then profit from the discount on these high-priced medications.…”
Section: Impac T Of 4 0 B On C Are Pat Tern Smentioning
confidence: 99%
“…Teaching hospitals may have different treatment patterns than nonteaching hospitals due to new knowledge acquired from clinical trials at their sites. Hospitals participating in the federal 340B program, which mandates manufactures to give deep discounts for outpatient drugs, may have different prescribing patterns than non‐340B hospitals due to lower drug acquisition costs and larger payment margins (Health Policy Brief, ; Jung, Xu, & Kalidindi, ). We stratified the sample by the type of hospital that the current oncologist was integrated with and constructed an IV as the initial oncologist's current integration with the same type of hospitals.…”
Section: Exploration Of the Treatment MIX Effectmentioning
confidence: 99%
“…Leveraging the Affordable Care Act's expansion of 340B to several types of non‐DSH hospitals—children's hospitals, critical access hospitals, and standalone cancer hospitals—Alpert et al 40 compare vertical integration of oncology practices between counties that contain newly eligible non‐DSH hospitals to those that do not, before and after 2010. Jung et al 5 use a similar identification strategy to estimate the effect of participating in 340B on where cancer patients received chemotherapy and spending in cancer. They compared outpatient hospital‐affiliated clinics where the 340B discounts apply to community clinics where the discounts do not apply.…”
Section: Introductionmentioning
confidence: 99%